2022
DOI: 10.3389/fnagi.2022.949763
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities volume and cognition: A meta-analysis

Abstract: BackgroundCerebral small vessel disease (CSVD) is prevalent in the elderly and leads to an increased risk of cognitive impairment and dementia. The volume of white matter hyperintensities (WMHs) increases with age, which affects cognition.ObjectiveTo explore the relationship between WMH volume and cognitive decline in patients with CSVD.MethodsWe performed a systematic search of PubMed, Embase, and the Web of Science databases from their respective creation dates to the 5 May 2022 to identify all the clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…A multivariate analysis incorporating WMH volume, WM volume, age, and education level identified both WMH volume and WM volume as independent risk factors for cognitive impairment. A previous meta-analysis demonstrated that WMH volume was associated with the risk of cognitive impairment and it supported our findings (Guo and Shi, 2022). A study on subclinical cerebral small vessel disease and processing speed in non-dementia patients (Hotz et al, 2021) revealed a correlation between WMH volume, normal WM volume and processing speed, also demonstrating that education level was a protective factor for WM volume and normal WM volume.…”
Section: Discussionsupporting
confidence: 90%
“…A multivariate analysis incorporating WMH volume, WM volume, age, and education level identified both WMH volume and WM volume as independent risk factors for cognitive impairment. A previous meta-analysis demonstrated that WMH volume was associated with the risk of cognitive impairment and it supported our findings (Guo and Shi, 2022). A study on subclinical cerebral small vessel disease and processing speed in non-dementia patients (Hotz et al, 2021) revealed a correlation between WMH volume, normal WM volume and processing speed, also demonstrating that education level was a protective factor for WM volume and normal WM volume.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, of all vascular phenotypes considered, WMH appeared to show the most robust associations with dementia risk, including AD, AD-meta, and all-cause dementia, adding evidence of causal associations to findings from observational studies and highlighting WMH as a key pathway to target for dementia prevention (eFigure 5 in Supplement 2). This finding reinforces earlier observations of a putative causal association of WMH with AD-meta, expanding it to a larger AD-meta GWAS and to clinically diagnosed AD .…”
Section: Discussionmentioning
confidence: 74%
“…Regarding the impact of white matter damage, there is a robust body of evidence to suggest that white matter damage results in cognitive impairment, although to our knowledge, this has not been comprehensively studied in dedicated large vessel occlusion stroke data sets yet. As an example, white matter damage is closely associated with cognitive impairment in patients with cerebrovascular small vessel disease 22 and traumatic brain injury. 23…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the impact of white matter damage, there is a robust body of evidence to suggest that white matter damage results in cognitive impairment, although to our knowledge, this has not been comprehensively studied in dedicated large vessel occlusion stroke data sets yet. As an example, white matter damage is closely associated with cognitive impairment in patients with cerebrovascular small vessel disease 22 and traumatic brain injury. 23 With regard to AIS specifically, Cha et al showed that unilateral spatial neglect seems to results from damage to white matter tracts such as the superior longitudinal fasciculus and forceps minor, 24 and Schevenels et al found that disruption of white matter tracts in patients with aphasic stroke results is negatively associated with language recovery in the first months after stroke.…”
Section: Discussionmentioning
confidence: 99%